Perlindungan Hukum Terhadap Hak Ekonomi Pemegang Hak Cipta Atas Mechanical Rights Yang Dikomersialkan Tanpa Izin: Studi Kasus Putusan Nomor 35/Pdt.Sus-Hak Cipta/2021/PN.Jkt.Pst - Ferdinand Yusuf Marcelino Sihite; Hernawan Hadi (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2024)
This research aims to analyze the extent of LMKN's authority to act as a legal protection institution for the economic rights of copyright holders and legal protection efforts for copyright violations, especially Mechanical Rights. This research is normative legal research that is prescriptive and applied with a case approach, namely examining one case of copyright infringement by duplicating songs/Musik without permission from the Creator and Owner of Related Rights as stated in the Decision of the Central Jakarta Commercial Court Number: 35 /Pdt.Sus-Copyright/2021/PN.Jkt.Pst. The collection of legal materials was carried out by conducting library studies and research on the legal sources used, namely primary and secondary legal materials. The analysis technique that the author uses is the syllogism method which is deductive, by submitting a major premise and a minor premise that connect each other to create a conclusion. Based on this research, the results obtained show that the LMKN which was created by the Government as a legal protection institution for copyright holders cannot fully become an institution that accommodates the rights of the Copyright Holders themselves. This is due to the limitations of LMKN which only deals with song copyrights of the Performing Rights type, while for Synchronization Rights and Mechanical Rights they must obtain permission directly from the Creator and Owner of the Related Rights. For this reason, in this writing the author includes Decision Number: 35/Pdt.Sus-Hak Copyright/2021/PN.Jkt.Pst. where in this case the resolution efforts that can be taken if a copyright violation occurs will be analyzed.